Does school social capital modify socioeconomic inequality in mental health? A multi-level analysis in Danish schools. (September 2015) - Nielsen, Line; Koushede, Vibeke; Vinther-Larsen, Mathilde; Bendtsen, Pernille; Ersbøll, Annette Kjær; Due, Pernille; Holstein, Bjørn E.
Abstract: It seems that social capital in the neighbourhood has the potential to reduce socioeconomic differences in mental health among adolescents. Whether school social capital is a buffer in the association between socioeconomic position and mental health among adolescents remains uncertain. The aim of this study is therefore to examine if the association between socioeconomic position and emotional symptoms among adolescents is modified by school social capital. The Health Behaviour in School-aged Children Methodology Development Study 2012 provided data on 3549 adolescents aged 11–15 in two municipalities in Denmark. Trust in the school class was used as an indicator of school social capital. Prevalence of daily emotional symptoms in each socioeconomic group measured by parents' occupational class was calculated for each of the three categories of school classes: school classes with high trust, moderate trust and low trust. Multilevel logistic regression analyses with parents' occupational class as the independent variable and daily emotional symptoms as the dependent variable were conducted stratified by level of trust in the school class. The prevalence of emotional symptoms was higher among students in school classes with low trust (12.9%) compared to school classes with high trust (7.2%) (p < 0.01). In school classes with low level of trust, the odds ratio for daily emotional symptoms was 1.89 (95% CI 1.25–2.86) in the low socioeconomic group compared to the high socioeconomic group. In school classes characterised by high and moderate trust, there were no statistically significant differences in emotional symptoms between high and low socioeconomic groups. Although further studies are needed, this cross-sectional study suggests that school social capital may reduce mental health problems and diminish socioeconomic inequality in mental health among adolescents. Highlights: One of the first studies on school social capital and adolescents' mental health. Level of trust in the school class was used as an indicator of social capital. High socioeconomic status was associated with fewer emotional symptoms. High trust in the school class was associated with fewer emotional symptoms. Classes with high trust had less socioeconomic inequality in emotional symptoms.